Implantación de la herramienta informática SISGER para automatizar los procesos de recaudación y distribución de agua en la Comisión de Usuarios de Agua El Moro - Valle Moche, 2016 - Palomino Becerra, Jean Marko (2017)
This research paper presents an alternative solution to the current situation of the Moche Valley, mainly in the Irrigation Commission El Moro, during the process of carrying out the schedules and distribution of water that are essential activities whose deficiency induce low efficiencies in the use of water, so that the inventory of the smaller Hydraulic Infrastructure will be updated to facilitate the administration and distribution of the water resource that has vital importance in the valley. This alternative consists on the development and implementation of a software that will support the management of water distribution in irrigation modules, this software is called SISGER (Irrigation Management System), its main features are the use of a web platform and a support Graphic (GIS); it is also formed by a recursive algorithm to accumulate the demands of irrigation in the distribution network, a database with the information of split plots, farming and distribution network with a friendly interface of consultation and generation of reports and graphs.The implementation of this software will allow us to evaluate the use of water resources in the Water Users’ Commission El Moro. One of the goals of this performance evaluation is providing information to irrigation managers and users organizations in order to improve water supply services to farmers.